2010
DOI: 10.1016/j.bbr.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal parathion exposure in rats causes sex-selective cognitive impairment and neurotransmitter defects which emerge in aging

Abstract: Developmental exposure of rats to the organophosphate (OP) pesticides leads to altered neurobehavioral function in juvenile and young adult stages. The current study was conducted to determine whether effects of neonatal parathion exposure on cognitive performance persist in older adult and aged rats, and the relationship of behavioral changes to underlying cholinergic and serotonergic mechanisms. We administered parathion to rat pups on postnatal days 1-4, at doses spanning the threshold for the initial signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 59 publications
1
43
0
Order By: Relevance
“…Future work should address whether premating and/or gestational exposure to secondhand smoke could result in earlier onset of the impairments associated with senescence. Indeed, we have already shown this to be the case for organophosphate pesticides, that like TSE, cause damage to ACh and 5HT circuits (Levin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Future work should address whether premating and/or gestational exposure to secondhand smoke could result in earlier onset of the impairments associated with senescence. Indeed, we have already shown this to be the case for organophosphate pesticides, that like TSE, cause damage to ACh and 5HT circuits (Levin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, only one sex may be sensitive to a specific exposure for a specific outcome. In animal studies, sex-selective disturbances in brain development and behavior have been reported for several pesticides including some organophosphates (Levin et al 2010), endosulfan (Lafuente and Pereiro 2013), prochloraz (Vinggaard et al 2005), and mixture of fungicides (Jacobsen et al 2012). In humans, sexually dimorphic response profiles have been reported in relation to prenatal exposure to endocrine disruptors.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-selective disturbances in brain development after gestational exposure have also been reported in animal studies of other organophosphates (Levin et al 2010) and for anti-androgenic fungicides (Bisenius et al 2006;Vinggaard et al 2005). …”
Section: Introductionmentioning
confidence: 93%
“…However, it became now clear that these agents act as developmental neurotoxicants through a number of differential mechanisms. Some of which operate at exposures below the threshold for cholinesterase inhibition may differ in their effects on brain development and their consequent impacts on behavioral performance (Paul et al 1994;Cohn and MacPhail 1997;Itoh et al 1997aItoh et al , 1997bPalumbo et al 2001;Castillo et al 2002;Levin et al 2002 Levin et al 2010). A series of studies with toxico-dynamically equivalent exposures in neonatal rats showed that chlorpyrifos, diazinon and parathion (PRT) elicit behavioral abnormalities in association with adverse effects on acetylcholine (ACh) and serotonin (5HT) circuits, but that the underlying defects and behavioral outcomes differ among the three OPs.…”
Section: Possible Mechanism Of Ecss-induced Autism and Developmental mentioning
confidence: 99%